Principles of risk management and insurance - Rejda, George E.; McNamara, Michael J.; Rabel, William H. (The Pearson series in finance, 2022)
Principles of risk management and insurance provides an in-depth examination of major risk themes. Using rich and up-to-date content on the basic concepts of risk and insurance, and introductory and advanced topics in traditional and enterprise risk management, the text is relevant to a wide number of disciplines in the business realm. Fully updated and revised, the 14th Edition covers global topics ranging from natural disasters and terrorism, to domestic issues like the ever-evolving Affordable Care Act and healthcare reform. Principles sets itself apart by placing primary emphasis on insurance consumers and blends basic riskmanagement and insurance principles with consumer considerations, allowing students to apply basic concepts to their own personal risk management and insurance programs.